Soil Characteristics and Productivity in Relation to Water Erosion on Sloping Lands in Foot-Hills of Shivaliks - MS Hadda; Sanjay Arora; DD Bhardwaj; Narinder Mohan (Journal of Soil and Water Conservation, 2022)
Water erosion being insidious in nature is serious menace in the foot-hills of Shivaliks. The study examined how soil morphological, chemical and physicaI characteristics and productivity are affected in upper and lower slope transects in the foot hills of Shiwaliks by water erosion. There is a tendency for decrease in water holding capacity, silt content, organic carbon, available N and P by 6.2, 33.3, 5.2, 12.6 and 20.5 per cent respectively in severely eroded A horizon as compared to moderately eroded A horizon of the pedons. The organic carbon, calcium carbonate, available N, P and K were lower by 16.6, 4 8.6, 32.8, 29.6, 22.4and 45.3%, respectively in upper slope transect over the lower slope transect in 10-60 cm soil depth. Similarly, total porosity, mean weight diameter, maximum water holding capacity, saturated hydraulic conductivity, plant available water, sand and clay contents were lower by 10, 31.3, 20.3, 7.1, 37-9, 12.6 and 10.5% , respectively in upper slope transect than that in lower slope transect in 10-60 cm soil depth . The three times lower infiltration rate was observed on the upper slope transect as compared to that on the lower slope transect. The productivity index ranged from 0.18 to 0.89 in the pedons. The maize grain yield decreased by 600.6 kg ha-1 on upper slope transect than that on lower slope transect. The results of study confirmed that the land degradation occurs first on steep land and then proceeds down the slope gradient.